Peran Perpustakaan Digital dalam meningkatkan Minat Literasi Masyarakat - Zami, Putri adz'biya Zam (Maliki Interdisciplinary Journal, 2025)
Digital libraries have an increasingly important role in improving people's literacy in today's information age. By providing easy and broad access to a wide range of resources, digital libraries enable individuals to access, understand, and utilize information more effectively. This article discusses the understanding of literacy, as well as how digital libraries contribute to fostering reading interest and critical thinking skills through diverse collections and interactive features. In addition, the article also identifies challenges faced by digital libraries, such as public awareness and internet access, as well as opportunities for collaboration with various parties to maximize positive impact in literacy. Thus, digital libraries serve not only as providers of information, but also as agents of change in building a more literate and knowledgeable society.